Public Private Partnership as a Public Service Dilemma - Setiawan, Tomi; F, Egnas Sukma (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
The change in the paradigm of governance currently demands the government to provide better service for the society. The availability of this service faces issues regarding limited government abilities, limited financial resources, and limited human resources management. This research was conducted on a Public Private Partnership between the Bandung City Government and PT Marga Tirta Kencana on their development and construction of the Cicadas Traditional Market. This study used a qualitative method. Informants were obtained by means of a purposive method through snowball technique. Research results indicate that this partnership is not mutually beneficial. This is due to a problem in the implementation of the partnership itself such as delays in development.